Sickle cell anemia complicated by Hepatitis E infection in pregnancy - Amatya, A; Choudhary, R; Zeher, S; Gurung, G; Rana, A (Journal of Institute of Medicine Nepal, 2008)
Case report: The hemoglobinopathies are a heterogeneous group of single-gene disorders that include the structural hemoglobin variants and the thalassemias. We present a rare case of sickle cell anemia in pregnancy in a young lady who was investigated in the line of jaundice due to hemolytic anemia (suspicion of hemolytic crisis) and associated with Hepatitis E IgM positivity who eventually had a fruitful pregnancy outcome with least maternal and neonatal morbidity. Key word: Hemoglobinopathies, Hepatitis E IgM positivity in pregnancy, Jaundice. The full text of this paper is available at Journal of Institute of Medicine website